ISLAMIC WORK ETHOS, ISLAMIC LEADERSHIP, AND EMPLOYEE PERFORMANCE - Robby Ardiansyah; Ina Ratnamiasih (Jurnal Riset Bisnis dan Manajemen, 2021)
Employee performance is a problem that has always been a priority for all organizations. This is also undeniable by agencies such as the Ministry of Religion in Sukabumi. In this study, employee performance is the main factor that is the concern of this study which is associated with Islamic Work Ethics and Islamic Leadership. The purpose of this study was to determine the influence of Islamic work ethic and Islamic leadership on the performance of employees of the Ministry of Religion in Sukabumi.The population of the study was 57 employees at the Ministry of Religion of Sukabumi with the sample taken using the census technique. The research method that was used is quantitative using verification and descriptive analysis. By using regression analysis and multiple correlations, it is known that Islamic work ethic and Islamic leadership have a large influence on employee performance with Islamic leadership having a greater influence than Islamic work ethic.